2021
DOI: 10.3390/microorganisms9061213
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Optimisation of Diesel Biodegradation at Low Temperatures by an Antarctic Marine Bacterial Consortium Isolated from Non-Contaminated Seawater

Abstract: Hydrocarbon pollution is widespread around the globe and, even in the remoteness of Antarctica, the impacts of hydrocarbons from anthropogenic sources are still apparent. Antarctica’s chronically cold temperatures and other extreme environmental conditions reduce the rates of biological processes, including the biodegradation of pollutants. However, the native Antarctic microbial diversity provides a reservoir of cold-adapted microorganisms, some of which have the potential for biodegradation. This study evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 102 publications
0
19
0
Order By: Relevance
“…Overall, RS treated at a higher temperature and more densely packed had better oil absorption. PBDs extend the analyses provided by OFAT as well as incorporating the possibility of two-way interactions between factors [26]. ANOVA confirmed that the model generated was highly significant overall, with R 2 = 0.9119, and the time of heating, packing density and oil concentration being significant factors (Table 5).…”
Section: Optimization Of Factors Affecting the Sorption Capacities And The Efficiency Of Oil/watermentioning
confidence: 61%
See 1 more Smart Citation
“…Overall, RS treated at a higher temperature and more densely packed had better oil absorption. PBDs extend the analyses provided by OFAT as well as incorporating the possibility of two-way interactions between factors [26]. ANOVA confirmed that the model generated was highly significant overall, with R 2 = 0.9119, and the time of heating, packing density and oil concentration being significant factors (Table 5).…”
Section: Optimization Of Factors Affecting the Sorption Capacities And The Efficiency Of Oil/watermentioning
confidence: 61%
“…Aligned factors from OFAT were further analyzed using Design-Expert software version 13.0 under the Factorial Miscellaneous Design (standard design) [26], with slight modifications. With a minimum of 11 horizontal factors, 6 center points were chosen.…”
Section: Response Surface Methodology (Rsm) Plackett-burman Design (Pbd)mentioning
confidence: 99%
“…To establish the settings that were nearest to optimal, each component was examined at two levels: low (−1) and high (+1) of its corresponding values (Table 7). Significant (p < 0.05) values were determined to profoundly impact the efficiency of diesel-seawater sorption and further analysis using CCD [65][66][67][68]. The PB factorial design at two levels was described by the following equation (Equation ( 3)):…”
Section: Plackett-burman (Pb) Designmentioning
confidence: 99%
“…The significant factors were analysed using one-way variance analysis (ANOVA) by GraphPad Prism 8.0.2 software (GraphPad Inc., San Diego, CA, USA). The influence of each parameter was tested using One-way ANOVA where significant and by pairwise post hoc comparisons using Tukey’s test [ 32 ].…”
Section: Methodsmentioning
confidence: 99%